Hubungan Durasi Tidur dengan Siklus Menstruasi pada Perawat Lansia di Innoshima Jepang - Rizha Chavina Nurfadhilah; Rani Safitri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Inadequate sleep duration has the potential to disrupt the stability of the neuroendocrine system and lead to irregularities in the menstrual cycle. This study aimed to identify the relationship between sleep duration and menstrual regularity in female nurses working in elderly care facilities in Innoshima, Japan. The study used a quantitative analytical approach with a cross-sectional design and involved 20 respondents. Data were obtained through a structured questionnaire and analyzed using the Chi-Square test, Fisher's Exact Test, and Pearson and Spearman correlations. The results showed that the majority of women with a sleep duration of ≥ 7 hours per night experienced regular menstruation (80%), while respondents with < 7 hours of sleep were dominated by cases of irregular menstruation (80%). Statistical tests yielded a value of p = 0.007 on Chi-Square, and a correlation coefficient of r = 0.600 with p = 0.005, indicating a moderate positive relationship between sleep duration and menstrual cycle regularity. These findings suggest that sleep duration should be considered as an early indicator in maintaining women's reproductive stability in a rotational work environment. Intervention in the work system and education on healthy sleep habits are important steps to protect the hormonal health of female workers.